An alternative route optimization handoff scheme for mobile IPV6 - Attir, Hisham Mostafa (2008)
Mobile nodes using MIPv6 suffer long handoff delays due to the Route Optimization registration process. Route Optimization eliminates the triangular routing effect faced in MIPv4. The long handoff latencies may cause severe performance degradation of transmission protocols such as TCP and UDP. Such negative effect can be reduced by some enhancements to the handoff procedure. FastRA, RA Caching, Advanced DAD, Optimistic DAD and Optimistic Node are some of the handoff schemes proposed to reduce the handoff latencies. The aim of this project is to propose an alternative approach to reduce the handoff latencies in MIPv6. Early Handoff (EH) is a handoff scheme that takes advantage of the coverage overlapping areas to perform earlier and smoother handoffs. Simulations using NS-2 and Mobiwan had been carried out to evaluate the performances of EH, FastRA and Optimistic Node. The simulations were conducted within addressing and security issues free environments using 1, 10, 20 and 30 Mobile Nodes settings. The results show that EH has achieved good results in terms of low handoff latency, low packets loss rate, low signaling load and good bandwidth per station when implemented in environments with little number of nodes. On the other hand, FastRA outperformed Optimistic Nodes and EH respectively when the number of Mobile Nodes exceeded 20 nodes.